2019
DOI: 10.1108/ijhrh-01-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Technological improvement in modern health care applications using Internet of Things (IoT) and proposal of novel health care approach

Abstract: Purpose With the development of emerging engineering technology and industrialization, there are greater changes in the life style of people in smart urban cities; therefore, there is also more chance of various health problems in urban areas. The life style of persons in metro urban areas with the expansive volume of population is similarly influenced by different application and administration frameworks. These are affecting the human health system up to an extended extent and there are more health-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 31 publications
(25 reference statements)
0
26
0
Order By: Relevance
“…• IOT -the Internet of things (Mattos et al, 2019;Heaton & Parlikad, 2019;Jan et al 2019;Rath & Pattanayak, 2019);…”
Section: Smart Technologymentioning
confidence: 99%
“…• IOT -the Internet of things (Mattos et al, 2019;Heaton & Parlikad, 2019;Jan et al 2019;Rath & Pattanayak, 2019);…”
Section: Smart Technologymentioning
confidence: 99%
“…IoT and large information advancements can be incorporated with keen well-being to address a portion of the difficulties to improve human services accessibility, access and expenses. Rath and Pattanayak (2019), with the improvement of rising building innovation and industrialization, showed that there are more prominent changes in the way of life of individuals in keen urban communities; in this way, there is additionally increasingly possibility of different medical issues in urban zones. A recreation was done to see the presentation of a well-being system in the proposed approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To induce intelligence, resource requires its own recognition, storage, scheduling, understanding of mobility patterns due to heterogeneity, incompleteness, uncertainty, and dynamism on the IoT paradigm . For the same, the authors have reviewed number of approaches and summarized that the semantic technologies with the use of ontologies help in classification of devices, semantic annotation, behavioral control, and coordination among components .…”
Section: Related Workmentioning
confidence: 99%
“…To induce intelligence, resource requires its own recognition, storage, scheduling, understanding of mobility patterns due to heterogeneity, incompleteness, uncertainty, and dynamism on the IoT paradigm. 1,2,3 For the same, the authors have reviewed number of approaches and summarized that the semantic technologies with the use of ontologies help in classification of devices, semantic annotation, behavioral control, and coordination among components. 4 Another solution is based on the usage of middle-ware approach, i.e., a declarative paradigm that provides application program interface (API), communication and other services as reconfigurable ubiquitous networked embedded systems (RUNES), and global enterprise resource integration (GERI).…”
Section: Related Workmentioning
confidence: 99%